Silencing of LncRNA C1RL-AS1 Suppresses the Malignant Phenotype in Gastric Cancer Cells via the AKT/β-Catenin/c-Myc Pathway - Zhen-Hua, Wu; Yi-Wei, Gong; Li-Qin, Zhao; Jie-Yun, Zhang; Zhe, Gong; Wei-Jian, Guo (Frontiers in Oncology, 2020)
Purpose: Numerous studies have shown that lncRNAs play vital roles in the development and progression of cancer. However, investigations of lncRNAs in gastric cancer are limited and need to be further pursued. Materials and Methods: According to RNA-seq results of gastric cancer (GC) tissues, we identified a novel lncRNA, C1RL-AS1. qRT-PCR was utilized to detect the expression level of C1RL-AS1 in paired GC and normal tissues. Nuclear/cytoplasmic fractionation was applied to evaluate the distribution of C1RL-AS1 in GC cells. For functional evaluation, CCK-8, colony formation, transwell and apoptosis assays were used to determine the oncogenic role of C1RL-AS1. Results: C1RL-AS1 was upregulated in GC tissues, and high expression levels of C1RL-AS1 were associated with poor prognosis. Further in vitro functional assays revealed that silencing C1RL-AS1 attenuated the proliferation rate and migration ability and enhanced the apoptotic rate and the senescence of gastric cancer cells. The subsequent underlying mechanistic investigation revealed that Wnt/β-catenin was involved in C1RL-AS1-mediated signaling. Rescue experiments suggested that C1RL-AS1 probably promoted the malignant phenotype via the AKT/β-catenin pathway by downregulating c-Myc. Conclusions: C1RL-AS1 probably exerts its biological function by mediating the AKT/β-catenin/c-Myc pathway, indicating a novel therapeutic target in GC.